Tingkat Keberhasilan Penanaman Mangrove Pada Lahan Bekas Tambang Timah Di Desa Rebo Kabupaten Bangka Sebagai Bentuk Pemanfaatan Lahan Dalam Wilayah Hutan Mangrove Di Pesisir Timur Pulau Bangka - Farhaby, Arthur Muhammad; Anwar, Muhammad Syaiful (Bioma : Berkala Ilmiah Biologi, 2021)
The existence of unconventional mines (TI) which is increasingly prevalent nowadays has penetrated the coast, resulting in the mangrove ecosystem unable to develop properly. One of the areas affected by unconvencional minning activities is on the coast of Takari Beach, Bangka Regency. Takari Beach is one of the areas located on the coast of Rebo Village, Sungailiat District, Bangka Regency. One of the rehabilitation efforts carried out is by planting mangrove seedlings on Takari Beach in 2018 with a total of 500 mangrove seedlings. Mangrove rehabilitation activities are one form of land use conducted in Takari Beach. This activity also needs to be supported by the maintenance and monitoring of planting results to determine the success rate of mangrove planting activities on ex-tin mining land located in the coastal area of Takari Beach, Bangka. The results showed that the percentage of mangroves living at the observation station, namely on plot 1, was 71%. Plot 2's survival rate is 80%. The survival rate for plot 3 is 81%, the survival rate for plot 4 is 54%, and the survival rate for plot 5 is 27%. Plots 1,2 and 3 have a high survival rate, which is around 70-81%. Plots 4, and 5 have a low survival rate, which is around 27-54%. This can indicate that the success rate of mangrove survival can be said to be less successful. This could be due to the fact that there are still floating unconventional mining (TI) activities, which are operating again so that it is suspected that the tailings yield inhibits the growth rate and causes the death of mangrove seedlings.